Local fiber orientation from X-ray region-of-interest computed tomography of large fiber reinforced composite components. (20th October 2019) - Baranowski, Thomas; Dobrovolskij, Dascha; Dremel, Kilian; Hölzing, Astrid; Lohfink, Günter; Schladitz, Katja; Zabler, Simon
Abstract: The local fiber orientation is a micro-structural feature crucial for the mechanical properties of parts made from fiber reinforced polymers. It can be determined from micro-computed tomography data and subsequent quantitative analysis of the resulting 3D images. However, although being by nature non-destructive, this method so far has required to cut samples of a few millimeter edge length in order to achieve the high lateral resolution needed for the analysis. Here, we report on the successful combination of region-of-interest scanning with structure texture orientation analysis rendering the above described approach truly non-destructive. Several regions of interest in a large bearing part from the automotive industry made of fiber reinforced polymer are scanned and analyzed. Differences of these regions with respect to local fiber orientation are quantified. Moreover, consistency of the analysis based on scans at varying lateral resolutions is proved. Finally, measured and numerically simulated orientation tensors are compared for one of the regions.